Law and Development of Middle-Income Countries : Avoiding the Middle-Income Trap - Peerenboom, R. P. (Randall P.), 1958-; Ginsburg, Tom (Cambridge : Cambridge University Press, 2014)
In 1960, there were 101 middle-income countries. By 2008, only thirteen of these had become high-income countries. Why do so many middle-income countries fail to develop after a promising start, becoming mired in the so-called middle-income trap? This interdisciplinary volume addresses the special challenges that middle-income countries confront from both a theoretical and a practical perspective. It is the first volume that addresses law and development issues in middle-income countries from the perspective of political, administrative and legal institutions and policies. The goal is to provide international development agencies and domestic policy makers with feasible recommendations to address the wide range of technically, politically and socially complex issues that middle-income countries face.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Law and economic development; Middle income countries